Electronic logbooks (e-logbooks) for the continuous assessment of medical licentiates and their medical skill development in the low-resource context of Zambia: A mixed-methods study - Barteit, Sandra; Schmidt, Jelena; Kakusa, Mwanja; Syakantu, Gardner; Shanzi, Aubrey; Ahmed, Yusuf; Malunga, Gregory; Blass, Klaus; Nieder, Jessica; Andreadis, Petros; Neuhann, Florian (Frontiers in Medicine, 2022)
Background: Countries in sub-Saharan Africa, continue to face insufficient health education resources and facilities, as well as a severe shortage of health care professionals. In 2019, the Levy Mwanawasa Medical University (LMMU) in Lusaka was launched to address the shortage of healthcare professionals implementing a decentralized training model utilizing selected regional and district hospitals in Zambia as training sites for various cadres. Decentralization makes it more challenging to monitor the learning process as part of continuous assessment; consequently, sufficient approaches are necessary to ensure the quality and quantity of medical skills training. Electronic logbooks (e-logbooks) provide a promising potential for transparent monitoring and evaluation of the medical training process. Objective: We designed and implemented an e-logbook for Medical Licentiate students based on an existing software system. We evaluated the feasibility of this e-logbook, its acceptability among a cohort of Medical Licentiate students and mentors, as well as its facilitators and barriers. Methods: During the course of a five week-long clinical rotation in a training site in Kabwe, Zambia, two mentors and ten students participated in the pilot study and its evaluation. A mixed-methods approach utilized log-based usage data from the e-logbook web platform and conducted semi-structured in-depth interviews. Results: Overall, both students and mentors accepted e-logbooks as a means to monitor skills development in this context, indicating that e-logbooks are a feasible tool in this decentralized setting. Feedback pointed out that the design and software-induced terminology of the e-logbook posed usability issues. The complexity and greater time commitment (mentors used a web-based platform instead of an app) limited the e-logbook's potential. Conclusion: We conclude that there is widespread acceptability of monitoring medical skill development through a tablet-based e-logbook. However, the e-logbook in its current form (based on an existing software system, with limited adaptation to the local context) was insufficient for the LMMU environment. Given that this was attributable to design flaws rather than technology issues or rejection of the e-logbook as a quality assessment tool in and of itself, we propose that the e-logbook be implemented in a co-design approach to better reflect the needs of students and mentors.